The factors that affect members’ use of a beauty industry matchmaking platform: Validation of the COM-B extended model - Chang, Yang-Wen; Hsu, Yen (Frontiers in Psychology, 2022)
The global impact of COVID-19 has seriously affected health and livelihood in every country or region, especially in terms of physical consumption behaviors. Hairdressing is an es-sential physical consumption behavior. To prevent infection, the consumption model for using the Beauty Industry Matchmaking Platform (BIMP) has been used during the pandemic. This study investigates the changes in the behavior of media app users in the beauty industry in the post-epidemic era of COVID-19. The COM-B model is the basis for a research framework to study the factors that affect changes in behavior in the areas of Capability, Motivation and Opportunity of the theoretical framework. A new dimension of fashion sense has expanded the application and validation of the COM-B model to determine the causal relationship between the ability to pursue beauty, motivation, fashion sense and opportunities by using the platform and the dimension of user behavior. The study finds that fashion sense in the BIMP has a positive and significant impact on beauty care ability, self-motivation to pursue beauty and future cooperation opportunities. The ability, moti-vation and opportunity to act are all positively significant, which is in agreement with the theo-retical framework of the COM-B model. There is no mediating effect for motivation between fashion sense and behavior. The results of this study show that increasing the sense of fashion for members using the BIMP will increases active behavior for members using the platform. This study also proposes practical suggestions for the operation of the BIMP based on the results.